Component Analysis of Main Categories of Reflective and Creative Approach to Teaching Medical Students - O V Razdorskaya (Peoples' Friendship University of Russia (RUDN University), 2014)
The results of system analysis of the notions "reflection" and "creativity" are presented, the peculiarities of their interrelation by the example of social and cultural aspect of a future health care provider's professional activity are defined.